The effect of green accounting and environmental performance on company profitability with corporate social responsibility (CSR) as a mediating variable - Muhamnad Ravi Kurniawan; Fenny Marietza (Jurnal Ekonomi, 2024)
The purpose of this study is to determine the effect of green accounting and environmental performance on profitability, using corporate social responsibility as a mediating variable. This study fills the empirical void left by previous studies that use legitimacy theory and signal theory to re-examine the effect of green accounting and environmental performance on profitability. This research is innovative because it sees corporate social responsibility as a mediator between green accounting and environmental performance on profitability. This study uses secondary data and quantitative methodology.Manufacturing companies listed on the Indonesia Stock Exchange (IDX) that actively participate in PROPER for the period 2018-2022 became the research population. A total of 200 observations from 40 companies that became the sample of this study met the criteria. The study's findings show that while green accounting has no bearing on profitability,  environmental performance has no bearing on profitability, CSR has no bearing on profitability, neither can it mediate the impact of green accounting on profitability nor that of environmental performance on profitability.